2022
DOI: 10.3390/nu14030479
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Ketogenic Diet on Adiponectin, Omentin and Vaspin in Children with Drug-Resistant Epilepsy

Abstract: Background: Changes in adipokine secretion may be involved in the anti-epileptic effect of a ketogenic diet (KD) in drug-resistant epilepsy (DRE). Objectives: The assessment of the influence of KD on serum adiponectin, omentin-1, and vaspin in children with DRE. Methods: Anthropometric measurements (weight, height, BMI, and waist-to-hip circumference ratio) were performed in 72 children aged 3–9 years, divided into 3 groups: 24 children with DRE treated with KD, 26—treated with valproic acid (VPA), and a contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 96 publications
0
14
0
Order By: Relevance
“…Consequently, the studies suggest that there is potential for an increase in the strength of the intervention groups' immune systems due to the intake of the ketogenic diet, unlike the control group. Finally, the average p-value of the research articles was p = 0.09, with 15 out of the 20 studies being considered as statistically significant in that that they had p values less than 0.05 at 95% CI [1], [2], [3], [4], [10], [11], [12], [13], [14], [15], [16], [19], [20], [21], [22]. For that reason, more than half of the research studies used in the current meta-analysis failed to reject their null hypotheses that the ketogenic diet had a positive effect on the human immune system.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the studies suggest that there is potential for an increase in the strength of the intervention groups' immune systems due to the intake of the ketogenic diet, unlike the control group. Finally, the average p-value of the research articles was p = 0.09, with 15 out of the 20 studies being considered as statistically significant in that that they had p values less than 0.05 at 95% CI [1], [2], [3], [4], [10], [11], [12], [13], [14], [15], [16], [19], [20], [21], [22]. For that reason, more than half of the research studies used in the current meta-analysis failed to reject their null hypotheses that the ketogenic diet had a positive effect on the human immune system.…”
Section: Resultsmentioning
confidence: 99%
“…Many healthcare systems are recently focusing on promoting healthy and balanced diets among populations to decrease their risk of experiencing chronic non-communicable diseases. By promoting the consumption of foods that are rich in a wide range of nutrients, healthcare systems have decreased the risk of populations getting ill, thereby decreasing the costs incurred due to the provision of patient care services to manage diseases such as diabetes, cancer, and heart conditions among others [1], [2], [4], [21]. However, to achieve such a goal, healthcare systems must illustrate the effectiveness of various diets and nutritional intakes in contributing towards an improved human immune system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adiponectin (GBP-28) is a protein hormone found in both white and brown adipose tissue and involved in the regulation of glucose levels as well as the breakdown of fatty acids [60]. It has three main polymeric forms: the low-(LMW), middle-(MMW), and high-molecularweight complexes (HMW) [61]. However, the reported expression levels of adiponectin vary.…”
Section: Pathogenesis Of Colorectal Cancermentioning
confidence: 99%
“…Xu et al found that both intranasal leptin delivery and direct injection of leptin into the cerebral cortex could result in partial excitatory inhibition of hypothalamic neurons, thus exerting an antiepileptic effect [ 12 ]. Besides, the antiepileptic effect of the ketogenic diet (KD) in drug-resistant epilepsy (DRE) also appears to be associated with adipocytokine levels [ 13 ].…”
Section: Introductionmentioning
confidence: 99%